2015
DOI: 10.1261/rna.052209.115
|View full text |Cite
|
Sign up to set email alerts
|

The Lsm1-7-Pat1 complex promotes viral RNA translation and replication by differential mechanisms

Abstract: The Lsm1-7-Pat1 complex binds to the 3 ′ end of cellular mRNAs and promotes 3 ′ end protection and 5 ′ -3 ′ decay. Interestingly, this complex also specifically binds to cis-acting regulatory sequences of viral positive-strand RNA genomes promoting their translation and subsequent recruitment from translation to replication. Yet, how the Lsm1-7-Pat1 complex regulates these two processes remains elusive. Here, we show that Lsm1-7-Pat1 complex acts differentially in these processes. By using a collection of well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…These findings lead to an interesting hypothesis that viruses generally recruit such mRNA surveillance machinery to promote their proliferation by effectively eliminating the defective RNAs or utilizing the RNA‐binding activity itself of Not4. Consistent with our hypothesis, brome mosaic virus (BMV) recruits the Lsm1‐7–Pat1 complex, a component of the deadenylation‐dependent mRNA decay machinery, for its genomic RNA translation and replication (Jungfleisch et al ., ). More recently, Meng and his colleagues demonstrated that the cytoplasmic exoribonuclease NbXRN4 also promotes BaMV accumulation in Nicotiana benthamiana (Lee et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings lead to an interesting hypothesis that viruses generally recruit such mRNA surveillance machinery to promote their proliferation by effectively eliminating the defective RNAs or utilizing the RNA‐binding activity itself of Not4. Consistent with our hypothesis, brome mosaic virus (BMV) recruits the Lsm1‐7–Pat1 complex, a component of the deadenylation‐dependent mRNA decay machinery, for its genomic RNA translation and replication (Jungfleisch et al ., ). More recently, Meng and his colleagues demonstrated that the cytoplasmic exoribonuclease NbXRN4 also promotes BaMV accumulation in Nicotiana benthamiana (Lee et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In general, defective viral RNAs are frequently synthesized by error-prone replicases during the RNA virus replication step (Domingo and Holland, 1997). These findings lead to an interesting hypothesis that viruses generally recruit such mRNA surveillance machinery to promote their proliferation by effectively eliminating the defective RNAs or (Jungfleisch et al, 2015). More recently, Meng and his colleagues demonstrated that the cytoplasmic exoribonuclease NbXRN4 also promotes BaMV accumulation in Nicotiana benthamiana (Lee et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Three unexpected factors were the decapping activators Lsm1–7, Pat1 and Dhh1. Depletion of the Lsm1–7, Pat1 or Dhh1 proteins dramatically reduced both BMV RNA translation and recruitment from translation to replication of the BMV RNA genomes [36,37,38,39,40,41]. Other components of the decay machinery are not required for these functions, indicating that BMV specifically subverts a selected group of decay factors [39].…”
Section: The Brome Mosaic Virus Converts Enemies Into Collaboratormentioning
confidence: 99%
“…Importantly, the Lsm1–7 Pat1 complex interacts in a RNAse-resistent manner with the BMV 1a, the solely viral protein required for recruiment. In line with this, the RNA-biding activity of the Lsm1–7/Pat1 complex is not requried for its function in recruitment [38]. The molecular mechanisms by which Dhh1 promotes BMV RNA recruitment remain uncharacterized.…”
Section: The Brome Mosaic Virus Converts Enemies Into Collaboratormentioning
confidence: 99%
“…However, no structures are available for Lsm1-7 bound to RNA, despite the central importance of this interaction in the mRNA decay pathway. In addition to activating mRNA decapping, Lsm1-7 has many other functions including formation of phase-separated processing bodies (P-bodies) (16,17), protecting 3′ ends of mRNA from 3′-5′ degradation by the exosome (18,19), stabilizing specific RNAs during starvation and autophagy (20), suppressing translation of stress-activated RNAs during osmotic shock (21), and promoting translation of viral RNAs (22). Human and S. pombe Lsm1-7 complexes bind tightly to oligouridylate (hereafter, oligoU) RNAs (12,23).…”
Section: Introductionmentioning
confidence: 99%